LEGAL REGULATION OF ENTREPRENEURIAL ACTIVITY - bayboboyeva, Firuza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The Economic Association of Interaction - individuals or legal entities, in order to combine the wines to maintain their independence, and the combined facilities. Corporation - for, to work in partnership to achieve common goals, united, independent legal entity - a legal person, the person described in the amount of medication. They are created in the form of joint stock companies. The concentration of enterprises is carried out in the form of cartel, syndicate, holding and financial-industrial groups.